Pengembangan E-Modul Pembelajaran Pendidikan Agama Islam pada Kelas XI di SMAN 10 Kota Bogor - Riska Oktavia; Sri Nurul Milla; Hambari (At-Tadris: Journal of Islamic Education, 2025)
Technological advancements demand continuous innovation in the development of interactive, flexible, and easily The advancement of technology demands the education sector to continuously innovate in the development of interactive, flexible, and easily accessible learning media. One such innovation is the e-module designed to support digital learning. This research aims to develop and test the feasibility of the e-module in PAI learning on the topic 'History of Islamic Civilization in Modern Times.' The method used is Research and Development (R&D) with the 4D development model, namely define, design, develop, and disseminate. The research was conducted on 11th-grade students at SMAN 10 Bogor City. The results from the media expert's assessment obtained an average score of 87.5%. The results from the content expert's assessment obtained an average score of 94%. And the results from the language expert's assessment obtained an average score of 83%. Based on these assessments, the PAI learning e-module is categorized as 'Very Valid' and is suitable for testing with students. The product trial was conducted in three stages, namely individual testing, small group testing, and large group testing. The individual test resulted in a score of 86%. The small group test achieved a score of 93%. And in the large group test, a score of 85% was obtained. Based on these results, the PAI e-module is categorized as "Very Valid". It can be concluded that the PAI e-module on the topic "Islamic Civilization in Modern Times" is suitable for use with 11th-grade students at SMAN 10 Kota Bogor.